2017
DOI: 10.1038/s41598-017-05066-w
|View full text |Cite
|
Sign up to set email alerts
|

Ancestor of land plants acquired the DNA-3-methyladenine glycosylase (MAG) gene from bacteria through horizontal gene transfer

Abstract: The origin and evolution of land plants was an important event in the history of life and initiated the establishment of modern terrestrial ecosystems. From water to terrestrial environments, plants needed to overcome the enhanced ultraviolet (UV) radiation and many other DNA-damaging agents. Evolving new genes with the function of DNA repair is critical for the origin and radiation of land plants. In bacteria, the DNA-3-methyladenine glycosylase (MAG) recognizes of a variety of base lesions and initiates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…The experimental results showed a decreased abundance of DNA gyrase along with the repression of cell division protein FtsZ (spot 1834; p-value = 4.788 × 10 −4 ) that influenced the low P. putida KT2440 growth level and as a consequence the low content of mcl-PHAs in bacterial cells. These observations were previously described by Guha et al [41], who showed that gyrase depletion altered ftsZ expression in Mycobacterium smegmatis, leading to slower growth. Furthermore, at the same time point (48 h), the abundance of DNA-3-methyladenine glycosylase (spot 2591; p-value = 0.003) was increased.…”
Section: Replication Transcription and Translationsupporting
confidence: 84%
See 1 more Smart Citation
“…The experimental results showed a decreased abundance of DNA gyrase along with the repression of cell division protein FtsZ (spot 1834; p-value = 4.788 × 10 −4 ) that influenced the low P. putida KT2440 growth level and as a consequence the low content of mcl-PHAs in bacterial cells. These observations were previously described by Guha et al [41], who showed that gyrase depletion altered ftsZ expression in Mycobacterium smegmatis, leading to slower growth. Furthermore, at the same time point (48 h), the abundance of DNA-3-methyladenine glycosylase (spot 2591; p-value = 0.003) was increased.…”
Section: Replication Transcription and Translationsupporting
confidence: 84%
“…Furthermore, at the same time point (48 h), the abundance of DNA-3-methyladenine glycosylase (spot 2591; p-value = 0.003) was increased. This protein participates in the initiation of the base excision repair process of damaged DNA [41].…”
Section: Replication Transcription and Translationmentioning
confidence: 99%
“…Potentially, retrotransposition appears to enrich the genome with large numbers of duplicate retrocopies that can act as a source for both new composite genes in the same species and new genomic sequences in foreign species. It should be noted that acquisition of intronless genes could occur without a reverse transcription event, possibly by introgression of bacterially encoded sequences in plant genomes, as it has been suggested in several studies (Emiliani et al, 2009; Yue et al, 2012; Yang et al, 2014; Hu et al, 2016; Fang et al, 2017).…”
mentioning
confidence: 89%
“…Evolutionary details of exon-intron organization in these genes are not analyzed comprehensively, although such an analysis would be rather informative and important for understanding their evolutionary history. Particularly, a series of papers on Phragmoplastophyta stress-related intron-containing genes show their origin by horizontal gene transfer of intronless prokaryotic genes (Emiliani et al, 2009; Fang et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation